Chain mediation of resourcefulness and self-perceived burden between coping styles and psychological distress in stroke patients: a cross-sectional study - Liu, Shuang; Huang, XianYi; Yue, Jie; Liu, Yan; Li, Yu; Chen, Li (Frontiers in Psychology, 2025)
ObjectiveTo explore the chain mediating roles of resourcefulness and self-perceived burden in the relationship between coping styles and psychological distress in stroke patients.MethodsThis study is a cross-sectional investigation conducted from April to December 2023. A convenience sample of hospitalized stroke patients (n = 432) was obtained in Sichuan Province, China. A demographic questionnaire, Medical Coping Mode Questionnaire, Resourcefulness Scale, Self-Perceived Burden Scale and psychological distress Thermometer were used to conduct the survey. Mediation effect testing was conducted using SPSS 25.0.ResultsCoping style, resourcefulness, self-perceived burden and psychological distress were significantly related to each other (p < 0.05). The chain mediation effects of resourcefulness and self-perceived burden between coping styles (confrontation and avoidance) and distress were significant.ConclusionResourcefulness and self-perceived burden mediated the relationship between coping styles (confrontation, avoidance) and psychological distress. The results imply that intervention from the perspective of coping style, resourcefulness and self-perceived burden may help to alleviate psychological distress in stroke patients.